Kočka a chrt: derridovská poznámka k estetice zvířat - Kolář, Martin (Filosoﬁcký časopis)
The starting point of our thinking is not only the post-human questioning of the animal – the “animot” – opened by Jacques Derrida in L’Animal que donc je suis and the actualization of the problem of logocentrism, but also the theme of the thinking of the other, or rather the “infinitely other” who is looking at me. And this also in the sense of a certain Lacanian notion of the mirror. Therefore, we will also focus on the problem of the gaze, the eye and the image in the sense of separation, as Michaela Fischer writes about it in Fragmentární vidění. Rancière, Derrida, Nancy (Fragmentary Vision. Rancière, Derrida, Nancy), and the making present of seeing, re-presentation and a certain archaeology and nostalgia from the point of view of Derrida in Mémoires d’aveugle. L’autoportrait et autres ruines. Our guides for this wandering about in the post-human world will be John D. Caputo’s The Prayers and Tears of Jacques Derrida, as well as Jacques Derrida’s cat and Michaela Fischer’s greyhound.